Trends, patterns and causes of respiratory disease mortality among inpatients in Tanzania, 2006–2015. Issue 1 (8th November 2018) - Kishamawe, Coleman; Rumisha, Susan F.; Mremi, Irene R.; Bwana, Veneranda M.; Chiduo, Mercy G.; Massawe, Isolide S.; Mboera, Leonard E. G.
Abstract: Objective: To determine the causes, patterns and trends of respiratory diseases‐related deaths in hospitals of Tanzania 2006–2015. Methods: Retrospective study involving 39 hospitals. Medical records of patients who died in hospital were retrieved, reviewed and analysed. Sources of data were hospital admission registers, death registers and International Classification of Diseases report forms. Information on demographic characteristics, date of death, the immediate underlying cause of death and co‐morbid conditions was collected. Results: Of the 247 976 deaths reported during the 10‐year period, respiratory diseases accounted for 12.92% ( n = 32 042). The majority of the respiratory mortality was reported among males (55.9%). Overall median age at death was 31 years with an interquartile range (IQR) of 1–47. Median age at death was significantly higher among males (35 years) than females (28 years) ( P < 0.0001). Most deaths (37.8%) occurred in eastern Tanzania. About one‐third (31.3%) of all respiratory mortality was reported among under‐five children, being among girls than boys (34.3% vs . 28.9%, χ 2 = 10.3, P < 0.0001). Adolescent and young adult females (15–29 years) had higher age‐standardised mortality rates per 100 000 due respiratory diseases than males. Pneumonia ( n = 16 639; 51.9%) and pulmonary tuberculosis ( n = 9687; 30.2%) accounted for the majority of deaths due to respiratory diseases. Significantly more females ( n = 7665; 54.5%) than males died from pneumonia ( n = 8878; 49.8%; χ 2 = 8.5, P < 0.0001). By contrast, significantly more males ( n = 6024; 34%) than females ( n = 3596; 26%; χ 2 = 15.5, P < 0.0001) died of tuberculosis. The proportion of death due to tuberculosis declined from 32.8% in 2006–2010 to 7.9% in 2011–2015. However, there was a significant increase in the proportion of death due to pneumonia from 49.6% in 2006–2010 to 53.4% in 2011–2015. Co‐morbid conditions contributed to 9.1% (2871/31 628) of all deaths due to respiratory diseases. The most common co‐morbid condition was HIV which accounted for 1735 (60.4%) deaths and was more common among males (60.8%; n = 957) than among females (59.7%; n = 764). Conclusions: Respiratory diseases account for a substantial proportion of all causes of hospital death in Tanzania. Pneumonia and tuberculosis contribute to more than three quarters of all deaths due to respiratory diseases. Since most major respiratory illnesses are avoidable, it is important to strengthen the capacity of the health delivery system in managing cases of respiratory diseases.